Agua basuras y alcantarillado: reciprocidad y políticas ambientales en un subrubio brasileño - Larrea Killinger, Cristina (ENDOXA, 2002)
The main purpose of this work is to analyse the relationship existing between reciprocity and moral by studying the main sanitation system, the drinking water supply, the sewerage, the drainage and garbage collecting in a brasilian suburb. We agree with the hypothesis that the lack of basic sanitation and/or aprecarious system genérate certain way of social exchange related to the system of circulation and distribution ofgoods andservices between people and the household units and to local political actions associated to some ideas about moral and poor people justice.